2021
DOI: 10.1021/acssuschemeng.1c04619
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Morphological Preservation and Redox Activity in Al-Incorporated NiFe2O4 for Chemical Looping Hydrogen Production

Abstract: Although chemical looping technology has enabled energy-efficient H2 production by combining separation and reaction through the lattice oxygen in oxygen storage materials (OSMs), metal oxides undergoing successive reduction–oxidation cycles generally suffer from a decline in long-term performance. This work investigates an Al-incorporated Ni-ferrite (NiFe2O4) particle to demonstrate a detailed deactivation mechanism induced by redox stress and suggests a strategy to prolong the lifespan of the particle. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…However, Fe was separated in the form of iron oxide after a number of cycles, causing the spinel structure to be destroyed. Lee et al [267] experimentally found that spinel-loaded oxygenates not only face the problem of phase separation, but also have the problems of surface grain aggregation and surface densification with the increasing number of cycles. These problems were effectively solved by introducing Al into the spinel to form a solid solution between the spinel and Al, which is beneficial for the long-term use of spinel oxygen carriers.…”
Section: Iron Based Oxygen Carriermentioning
confidence: 99%
“…However, Fe was separated in the form of iron oxide after a number of cycles, causing the spinel structure to be destroyed. Lee et al [267] experimentally found that spinel-loaded oxygenates not only face the problem of phase separation, but also have the problems of surface grain aggregation and surface densification with the increasing number of cycles. These problems were effectively solved by introducing Al into the spinel to form a solid solution between the spinel and Al, which is beneficial for the long-term use of spinel oxygen carriers.…”
Section: Iron Based Oxygen Carriermentioning
confidence: 99%
“…10,11 The oxygen transfer between the fuel reactor (FR), steam reactor (SR), and air reactor (AR) through OCs achieves the synergistic production of high-purity hydrogen with the internal separation of CO 2 . 12,13 In the previous study, 14 we proposed a novel CL cascade-coupled hydrogen generation (CL-CCHG) process to achieve efficient conversion and purification of hydrogen-rich syngas obtained from an auto-thermal CL reforming (CLRa) or CL gasification (CLG) process at the front end (Figure S1). This process avoids the use of water gas shift catalysts and CO 2 adsorbents, significantly reducing the energy consumption and cost of the post-treatment step.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical looping (CL) is a novel alternative technology that uses oxygen carriers (OCs) to break down chemical reactions into multiple sub-reactions, optimizing material and energy distribution to achieve low cost and low emissions. CL hydrogen generation (CLHG) is an energy-efficient, safe, and low-cost route. , The oxygen transfer between the fuel reactor (FR), steam reactor (SR), and air reactor (AR) through OCs achieves the synergistic production of high-purity hydrogen with the internal separation of CO 2 . , In the previous study, we proposed a novel CL cascade-coupled hydrogen generation (CL-CCHG) process to achieve efficient conversion and purification of hydrogen-rich syngas obtained from an auto-thermal CL reforming (CLRa) or CL gasification (CLG) process at the front end (Figure S1). This process avoids the use of water gas shift catalysts and CO 2 adsorbents, significantly reducing the energy consumption and cost of the post-treatment step.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One challenging issue in the chemical looping is introducing suitable redox catalysts. , Specifically, redox catalysts for CLWS should satisfy the requirements of not only high oxygen carrying capacity and redox kinetics but also high reactivity toward H 2 O. Additionally, they should be extremely coke-resistant during fuel combustion to enhance H 2 purity. , Furthermore, the crystalline structure should be maintained under a steam condition as well as under repeated redox cycles . Developing suitable redox catalysts thus will lead to sustainable production of high-purity H 2 , and accordingly, it has long been pursued.…”
Section: Introductionmentioning
confidence: 99%